Chelate‐Thiolate‐Coordinate Ligands Modulating the Configuration and Electrochemical Property of Dinitrosyliron Complexes (DNICs). Issue 45 (25th September 2015) - Yeh, Shih‐Wey; Lin, Chih‐Wei; Liu, Bai‐Heng; Tsou, Chih‐Chin; Tsai, Ming‐Li; Liaw, Wen‐Feng
Abstract: As opposed to the reversible redox reaction ({Fe(NO)2 } 10 reduced‐form DNIC [(NO)2 Fe(S(CH2 )3 S)] 2− (1 )⇌{Fe(NO)2 } 9 oxidized‐form [(NO)2 Fe(S(CH2 )3 S)] − ), the chemical oxidation of the {Fe(NO)2 } 10 DNIC [(NO)2 Fe(S(CH2 )2 S)] 2− (2 ) generates the dinuclear {Fe(NO)2 } 9 –{Fe(NO)2 } 9 complex [(NO)2 Fe(μ‐SC2 H4 S)2 Fe(NO)2 ] 2− (3 ) bridged by two terminal [SC2 H4 S] 2− ligands. On the basis of the Fe K‐edge pre‐edge energy and S K‐edge XAS, the oxidation of complex 1 yielding [(NO)2 Fe(S(CH2 )3 S)] − is predominantly a metal‐based oxidation. The smaller S1‐Fe1‐S2 bond angle of 94.1(1)° observed in complex 1 (S1‐Fe1‐S2 88.6(1)° in complex 2 ), compared to the bigger bond angle of 100.9(1)° in the {Fe(NO)2 } 9 DNIC [(NO)2 Fe(S(CH2 )3 S)] −, may be ascribed to the electron‐rich {Fe(NO)2 } 10 DNIC preferring a restricted bite angle to alleviate the electronic donation of the chelating thiolate to the electron‐rich {Fe(NO)2 } 10 core. The extended transition state and natural orbitals for chemical valence (ETS‐NOCV) analysis on the edt‐/pdt‐chelated {Fe(NO)2 } 9 and {Fe(NO)2 } 10 DNICs demonstrates how two key bonding interactions, that is, a FeS covalent σ bond and thiolate to the Fe d   z   2 charge donation, between the chelating thiolate ligand and the {Fe(NO)2 } 9/10 core could be modulated by the backbone lengths of the chelating thiolate ligands to tune the electrochemical redox potential ( E 1/2 =−1.64 V for complex 1 and E 1/2 =−1.33 V for complex 2 ) and to dictate structural rearrangement/chemical transformations (S‐Fe‐S bite angle and monomeric vs. dimeric DNICs). Abstract : Good two NO : The physical properties and the chemical reactivity of the {Fe(NO)2 } 10 DNICs [(NO)2 Fe(S(CH2 ) n S)] 2− ( n =3 (pdt=1, 3‐propanedithiolate); n =2 (edt=1, 2‐ethanedithiolate), see scheme) were demonstrated to be modulated by the backbone lengths of the chelating thiolate ligands. It was shown that the FeS covalent bond and the thiolate to the Fe d   z   2 charge donation modulate the reduction potentials and the chemical transformations.